Implementasi PMA Nomor 8 Tahun 2018 Oleh Penyelenggara Perjalanan Ibadah Umrah (Studi Kasus PPIU PT. Solusi Balad Lumampah) - M Izzul Mutho; Asep Syarifuddin Hidayat (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2019)
AbstractThis study seeks to analyze the implementation of PMA Number 8 of 2018 which is a revised result of PMA Number 18 of 2015 by looking at legal cases that ensnare PPIU Lumadah Balad Solutions. PT. SBL in running its business provides low-cost Umrah, bonuses for agents, and provides an installment mechanism. According to the Financial Services Authority (OJK) they must subsidize Umrah promo pilgrims and cover the costs of pilgrims who have left. Here there is a miss management as conveyed by the Financial Services Authority (FSA), mainly related to the ponzi scheme that is run. There are many shortcomings in PMA Number 18 Year 2015 as a regulation that makes PT. SBL failed to dispatch the congregation. Among these are the reporting mechanism as in article 25 paragraph 2 which makes this regulation considered passive. Add to this the lack of oversight by the government and the cost standards not yet specified in this PMA. This then resulted in a revision effort by the Government by making additional regulations, namely PMA Number 8 of 2018. In it set reference fees for Umrah pilgrims, the maximum limit of departure and also the prohibition of PPIU to dispatch their pilgrims using bailout funds as in article 12.Keywords: PMA, PT. SBL, Implementation